Livestock Disease and Health Care Facility in Sundarbans Delta of India - Samares Kumar Das and Hema Tripathi, (Indian Journal of Extension Education, 2013)
There are a number of livestock diseases which are seasonal in nature. Understanding the disease pattern and health carefacility has an implication in formulating an efficient and effective disease management strategy. With this implication, astudy was conducted in four villages of Sundarban delta of India to understand the prevalence of livestock disease, theirseasonality, and health care facility available. A participatory case study method was used for the study. Data werecollected using semi-structured interview, listing, narrative and observation method. Study reveals that foot and mouthdisease, ranikhet disease, chicken pox, hump sore, etc. were highly seasonal, whereas amphistomiasis, delayed expulsionof placenta, dystokia, etc. were not seasonal. Quacks, veterinary officers, medicine pedlars, medicine shop keepers, midwives, and ethno-veterinarians were the veterinary service providers in the study area. It is concluded that a holisticresearch is needed on documentation and validation of major livestock diseases in order to suggest effective diseasemanagement practices in the context of prevailing health care practices and available veterinary facilities.